2004
DOI: 10.1051/0004-6361:20035771
|View full text |Cite
|
Sign up to set email alerts
|

A multifrequency analysis of radio variability of blazars

Abstract: Abstract.We have carried out a multifrequency analysis of the radio variability of blazars, exploiting the data obtained during the extensive monitoring programs carried out at the University of Michigan Radio Astronomy Observatory (UMRAO, at 4.8, 8, and 14.5 GHz) and at the Metsähovi Radio Observatory (22 and 37 GHz). Two different techniques detect, in the Metsähovi light curves, evidence of periodicity at both frequencies for 5 sources (0224 + 671, 0945 + 408, 1226 + 023, 2200 + 420, and 2251 + 158). For th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
63
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 44 publications
22
63
0
2
Order By: Relevance
“…This is consistent with the results of Ciaramella et al (2004), who found periodic behaviour in about 4% of their irregularly sampled blazar light curves spanning several decades. For most sources, the A107, page 16 of 25 time scales are too long or the variability is too complex to fit our simple models.…”
Section: Caveatssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the results of Ciaramella et al (2004), who found periodic behaviour in about 4% of their irregularly sampled blazar light curves spanning several decades. For most sources, the A107, page 16 of 25 time scales are too long or the variability is too complex to fit our simple models.…”
Section: Caveatssupporting
confidence: 92%
“…Studies of radio source variability in the radio-to-millimetre regime on time-scales up to several decades have been facilitated by monitoring programmes targeting medium or large source samples selected by known variability (Aller et al 1996;Tornikoski et al 1996;Aller et al 1999;Stevens et al 1994), radio spectrum (Valtaoja et al 1992;Teraesranta et al 1998;Nieppola et al 2007), or gamma-ray brightness (Fuhrmann et al 2007, and in prep.). Discussions of blazar variability have mostly been focused on understanding the characteristics of flares, which are observed on time scales ranging from one day or less (Wagner et al 1995) to weeks or months (e.g., Angelakis et al 2012) to several years ), and their interpretation in the framework of jet models (e.g., Valtaoja et al 1999;Türler et al 2000;Ciaramella et al 2004;Hovatta et al 2009;Angelakis et al 2012). While it is generally accepted that shock-produced flares dominate the variability on very short time scales (days to weeks), geometric variability should have an effect on longer time scales because rotation or precession, as suggested by VLBI observations of many jets (e.g., Kellermann et al 2004), would inevitably lead to changes in Doppler boosting of the radiative zones in the jet.…”
Section: Introductionmentioning
confidence: 99%
“…The time series analysis performed by Villata et al (2004a) showed that the main radio outbursts repeat every ∼8 years (see also Ciaramella et al 2004), with a possible progressive stretching of the period. Moreover, when considering the best-sampled time interval 1994-2003, the optical light curve was found to correlate with the radio hardness ratios, with a radio time delay of about 100 days.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, it was fruitfully applied in volcanic environment [8,13], physics of musical instruments [12,14,15] and dynamical systems in mixtures [16]. Moreover, further studies have been conducted on signals recorded in real environments with delay and reverberation (e.g., convolutive mixtures) [17,18].…”
Section: The Ica Methodsmentioning
confidence: 99%
“…The point of PSNR at which the second derivative attains its maximum is the measure of the noise strength. The practical solution of filtering the random noise has been obtained through the use of Robust Principal Component Analysis Neural Network [14].…”
Section: Noise Reductionmentioning
confidence: 99%